LEADERSHIP AND CHINA philosophy, place and practice. - Bathurst, Ralph; Chen, Michelle Sitong ([S.l.] : ROUTLEDGE, 2022)
Since its opening in 1978, China has undergone radical change. By establishing special economic zones along its Eastern coastal borders under Deng Xioping's tutelage, China entered the global market. Loosening controls from central government allowed for a more free-market approach that facilitated easier trading partnerships across national boundaries. Leadership and China: Philosophy, Place and Practice explores the impact of these changes today. Companies across the globe are doing business with Chinese counterparts, but recently the Western world has begun treating China with suspicion, with some commentators claiming nefarious aims on the part of Chinese Communist Party, and intentions of favoring China's growing middle class and political elites, while impoverishing other international trading partners. This calls for wise leadership on both sides of the political divide and this book facilitates conversations that explore synergies between East and West, aiming to move past suspicion and discuss how leaders might work for the benefit of all humanity. With an orientation towards conversations rather than polemics, graduate students, scholars and business leaders across the globe will benefit from this book.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / International / General; Leadership -- China; International trade; China -- Economic conditions